Role Definitions and Organizational Citizenship Behavior: The Importance of the Employee's Perspective - Morrison, Elizabeth Wolfe (Academy of Management Journal, 1994)
A survey of 317 clerical workers demonstrated that employees differed in what they defined as in-role and extra-role behavior, that these differences were related to commitment and social cues, and that employees were more likely to display organizational citizenship behavior (OCB) if they defined the behavior as in-role rather than extra-role. Results indicate that the boundary between in-role and extra-role behavior is not clearly defined and that OCB is a function of how broadly employees define their job responsibilities. This study suggests the need for a reconceptualization of OCB.